THE ROLE OF READING CORNER IN INCREASING CREATIVITY AND INDEPENDENCE OF CLASS VIII STUDENTS AT MTs FUTUHIYYAH BANGOREJO: PERAN POJOK BACA DALAM MENINGKATKAN KREATIVITAS DAN KEMANDIRIAN SISWA KELAS VIII MTs FUTUHIYYAH BANGOREJO - Siti Khusnaini; Yuli Kartika Efendi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2023)
This research was motivated by the problem of student’s lack of creativity and independence in the learning process in class. This in fluenced by student literacy wich tends to be low. The literacy movement program currently being promoted in schools is the reading sorner. This research aims to determine the role of reading corners in increasing students’ creativity and independence. This research uses descriptive qualitative methods. The subjects of this research are class VIII Students at MTs Futuhiyyah Bangorejo, the object of this research is the reading corner in clas VIII. Based on the research conducted, it was concluded that the reading corner had an influence on students’ creatifity and independence. Reading corner really help teachers to get students used to being active and developing their thinking abilities, knowing the direction and goals of their learning so they don’t depend on the teacher.